Correction: Immature dendritic cells navigate microscopic mazes to find tumor cells. Issue 18 (30th August 2019) - Um, Eujin; Oh, Jung Min; Park, Juhee; Song, Taegeun; Kim, Tae-Eon; Choi, Yongjun; Shin, Changsik; Kolygina, Diana; Jeon, Jae-Hyung; Grzybowski, Bartosz A.; Cho, Yoon-Kyoung
Abstract : Correction for 'Immature dendritic cells navigate microscopic mazes to find tumor cells' by Eujin Um et al., Lab Chip, 2019, 19, 1665–1675.